Diaphragmatic Hernia Associated With Absent Ductus Venosus and Anomalous Connection of an Obliterated Umbilical Vein to the Coronary Sinus. Issue 4 (July 2020) - Chen, Peter C.; Swanson, Julia C.; Masand, Prakash; Rodriguez, Jose R.; Mery, Carlos M.
Umbilical vein anomalies are a rare congenital defect, which have been associated with absent ductus venosus, with few cases also involving a congenital diaphragmatic hernia. We describe a case of postnatal development of an anterior diaphragmatic hernia of Morgagni in a four-year-old patient diagnosed prenatally with mesocardia, absent ductus venosus with a large umbilical vein, a large secundum atrial septal defect, and patent ductus arteriosus.